The mediating role of psychological commitment between recreation specialization and life satisfaction: Evidence from Xiamen Marathon runners - Tian, Haibo; Zhou, Wenting; Qiu, Yajun (Frontiers in Psychology, 2022)
Although previous research spared no efforts to explain the life satisfaction of marathon runners, little was known about the relationship between recreation specialization (RS), life satisfaction (LS), psychological commitment (PC), and social support (SS). This study examines (i) how the dimension of RS (i.e., behavior, cognition, and affect) influences runners’ PC and LS, and (ii) the mediating effects of PC and the moderating effects of SS on the relationship between behavior, cognition, affect, and LS. The results showed that behavior (β = 0.15, p < 0.01), cognition (β = 0.35, p < 0.001), affect (β = 0.28, p < 0.001), and PC (β = 0.59, p < 0.001) had significant and positive impacts on runners’ LS; PC (Indirect path coefficient = 0.09 0.20) mediated the relationship between the dimensions of RS and LS. In addition, the results also confirmed the moderating effects of SS (β = 0.10, p < 0.05) between affect dimension and LS. These findings offered more evidence for understanding how RS dimensions and PC influence runners’ LS. Future research should integrate runner’s leisure experiences to better understand the results revealed in this study.